2021
DOI: 10.3390/ijms22105386
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin Alternatively Modifies Mitochondrial Dynamics in Dendritic Cells to Reduce Kidney Ischemic Reperfusion Injury

Abstract: Dendritic cells (DCs) are unique immune cells that can link innate and adaptive immune responses and Immunometabolism greatly impacts their phenotype. Rapamycin is a macrolide compound that has immunosuppressant functions and is used to prevent graft loss in kidney transplantation. The current study evaluated the therapeutic potential of ex-vivo rapamycin treated DCs to protect kidneys in a mouse model of acute kidney injury (AKI). For the rapamycin single (S) treatment (Rapa-S-DC), Veh-DCs were treated with r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…Seahorse Assay, Mitochondrial DNA Quantification, and Transmission Electron Microscopy HK-2 cells were transferred to a Seahorse 24-well tissue culture plate, oxygen consumption rate was measured, and parameters were calculated as described in our previous work. 33,34 Total DNA was extracted from Boston University mouse proximal tubular cells by incubating cells in sodium dodecyl sulfate lysis buffer with proteinase K overnight at 55°C followed by ethanol precipitation. The abundance of mitochondrial DNA was quantified using RT-PCR by assessing the ratio of mouse mitochondrially encoded nicotinamide adenine dinucleotide N1hydrogen dehydrogenase, subunit 1 (ND1) relative to mouse nuclear DNA HK-2.…”
Section: Primary Tubular Cell Culture and Transductionmentioning
confidence: 99%
“…Seahorse Assay, Mitochondrial DNA Quantification, and Transmission Electron Microscopy HK-2 cells were transferred to a Seahorse 24-well tissue culture plate, oxygen consumption rate was measured, and parameters were calculated as described in our previous work. 33,34 Total DNA was extracted from Boston University mouse proximal tubular cells by incubating cells in sodium dodecyl sulfate lysis buffer with proteinase K overnight at 55°C followed by ethanol precipitation. The abundance of mitochondrial DNA was quantified using RT-PCR by assessing the ratio of mouse mitochondrially encoded nicotinamide adenine dinucleotide N1hydrogen dehydrogenase, subunit 1 (ND1) relative to mouse nuclear DNA HK-2.…”
Section: Primary Tubular Cell Culture and Transductionmentioning
confidence: 99%
“…In this study, the mechanism of MCU-mediated mitochondrial damage remains a mystery. A large number of studies reported in recent years that mitochondrial quality control is an important mechanism involved in the pathogenesis, injury, and recovery of AKI [17][18][19][20][21]. Mitochondrial dynamics has been considered to be a crucial component of mitochondrial quality control and may be associated with MCU.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence from animal studies that other acute kidney injury (AKI) induced by multiple pathogenic factors such as I/R, cisplatin, sepsis, folic acid, and rhabdomyolysis are associated with mitochondrial dynamics, including ssion and fusion [17][18][19][20][21]. Mitochondrial dynamics is an important part of mitochondrial quality control, which is responsible for maintaining the relative stability of mitochondrial quantity, morphology and function, that is, mitochondrial homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…Following this, cells were washed (2×) and cocultured with iMSC or cultured as a monoculture. Cocultured THP-1 cells were transferred to a Seahorse 24-well tissue culture plates and oxygen consumption rate (OCR) was measured, and parameters were calculated as previously described [ 24 ]. Briefly, prior to the assay, the media was changed to unbuffered DMEM (Gibco #12800-017, pH 7.4, 37 °C), and cells were equilibrated for 1 h at 37 °C.…”
Section: Methodsmentioning
confidence: 99%